Pharmacists’ views on involvement in pharmacy practice research: Strategies for facilitating participation - Armour, Carol (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
In order for community pharmacy practice to continue to evolve, pharmacy practice research on potential new services is essential. This requires the active participation of community pharmacists. At present the level of involvement of community pharmacists in pharmacy practice research is minimal. OBJECTIVES: To ascertain the attitudes of a group of research-experienced community pharmacists towards participating in research; to investigate the barriers and facilitators to participation; to identify potential strategies to increase the involvement of community pharmacists in research. METHODS: A focus group was conducted with a purposive sample of 11 research-experienced community pharmacists. A pharmacist academic moderated the focus group using a semi-structured interview guide. The participants were asked about their attitudes towards research, previous involvement in research, barriers to their involvement and strategies to overcome these barriers. The session was audio-taped and notes were taken by an observer. Thematic analysis of the notes and audio-tape transcripts was conducted. RESULTS: Three themes emerged around pharmacists’ attitudes towards research: pharmacists’ perception of the purpose of research, pharmacists’ motivation for involvement in research, and pharmacists’ desired role in research. Barriers to research participation were grouped into four themes: pharmacists’ mindset, communication, infrastructure (time, money and staff), and skills/knowledge. Strategies to address each of these barriers were suggested. CONCLUSIONS: Participants recognised the importance of research towards advancing their profession and this was a motivating factor for involvement in research. They perceived their role in research primarily as data collection. A series of practical strategies to overcome the barriers to participation were offered that researchers may wish to consider when promoting research outcomes and designing research projects.